Range of Normal Liver Stiffness and Factors Associated With Increased Stiffness Measurements in Apparently Healthy Individuals - Bazerbachi, F.; Haffar, S.; Wang, Z.; Cabezas, J.; Arias-Loste, M.; Crespo, J.; Darwish-Murad, S.; Ikram, M.; Olynyk, John; Gan, E.; Petta, S.; Berzuini, A.; et al. (W.B. Saunders Co, 2019)
Background & Aims: Transient elastography (TE) is a noninvasive technique used to measure liver stiffness to estimate the severity of fibrosis. The range of liver stiffness measurements (LSMs) in healthy individuals is unclear. We performed a systematic review to determine the range of LSMs, examined by TE, in healthy individuals and individuals who are susceptible to fibrosis. Methods: We collected data from 16,082 individuals, in 26 cohorts, identified from systematic searches of Embase, Ovid MEDLINE, Cochrane Central Register of Controlled Trials, and Cochrane Database of Systematic Reviews for studies of liver stiffness measurements. Studies analyzed included apparently healthy adults (normal levels of liver enzymes, low-risk alcohol use patterns, and negative for markers of viral hepatitis). The presence of diabetes, hypertension, dyslipidemia, or steatosis, based on ultrasound examination, was known for most participants. We performed a meta-analysis of data from individual participants. The cohort was divided into 4 groups; participants with a body mass index <30 kg/m2 were examined with the medium probe and those with a body mass index =30 kg/m2 were examined with the extra-large probe. Linear regression models were conducted after adjusting for potential confounding factors of LSMs. We performed several sensitivity analyses. Results: We established LSM ranges for healthy individuals measured with both probes—these did not change significantly in sensitivity analyses of individuals with platelets =150,000/mm3 and levels of alanine aminotransferase =33 IU/L in men or =25 IU/L in women. In multivariate analysis, factors that modified LSMs with statistical significance included diabetes, dyslipidemia, waist circumference, level of aspartate aminotransferase, and systolic blood pressure at examination time. Significant increases in LSMs were associated with the metabolic syndrome in individuals examined by either probe. Diabetes in obese individuals increased the risk of LSMs in the range associated with advanced fibrosis. Conclusions: In a systematic review and meta-analysis of data from individual participants, we established a comprehensive set of LSM ranges, measured by TE in large cohorts of healthy individuals and persons susceptible to hepatic fibrosis. Regression analyses identified factors associated with increased LSMs obtained by TE with the medium and extra-large probes.